BENJAMIN Z. KEDAR, PETER HERDE, A Bavarian Historian Reinvents Himself: Karl Bosl and the Third Reich: Jerusalem 2011, Hebrew University Press Magnes, 164 s. - Dobeš, Jan (Dějiny – teorie – kritika, 2012)
Recenze